(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
At present, a quality costing method is not sufficiently widespread in the practice of Ukrainian enterprises, including contractors. This leads to an understanding of the existence of factors that restrain its application in practice. Moreover, the influence of peculiarities of construction activity on the methodology of quality cost accounting has been defined. The non-adaptation of the method to the specifics of the construction sector reduces its attractiveness for contractors. That’s why the purpose of the on-going paper is to study and systematize the problematic aspects of the implementation of the quality costing method based on the Prevention, Appraisal and Failure Model taking into account the influence of construction activity. The difficulties are considered in frames of each of the categories within cost of quality. Besides, it was found that the general problems that apply to all categories of quality costs include a subjective approach to attributing data to quality costs, their dispersal in the traditional accounting system of the enterprise, the lack of adaptation of the structure of the categories of expenses by the optimal amount and the reflection of the specifics of the construction activity. The measurement problem is inherent in all categories apart from external deficiencies and manifests itself in relation to preventive costs and assessment costs - in the absence of a direct link between activities and consumed resources, and also a subjective approach to categorizing costs into Prevention or Appraisal categories. In the case of internal losses, this is the presence of hidden losses. The long construction cycle generates a prolonged appearance of costs of external defects in the accounting system. This caused the necessity to adopt quality costing by means of exclusion of the costs for external defects from the short-term analysis. Ignoring the problem solving of the method may result in distortion of management information and losing of its usefulness. This is also important for the adaptation of the general methodology to the specifics of the construction activity and the development of appropriate methodological recommendations.